Development of PjBL e-modules based on ispring suite on alternative energy sources of water for elementary students - Pratama, Yogi; Kumala, Farida Nur; Yasa, Arnelia Dwi (Jurnal Bidang Pendidikan Dasar, 2024)
The aim of this research is to implement the results of the E-Module and determine the media development, feasibility and practicality of the E-Module. The type of research used in this research is the ADDIE development model. The subjects of this research were teachers and students of class VI using the questionnaire method with data collection tools in the form of questionnaires and documentation. The research results showed that the E-Module was declared very feasible based on media experts at 97.5%, material experts at 92.5% and language experts at 95.8% so that the learning media was suitable for testing. The practicality test given by the teacher obtained 94.5%, 95.1% for students in small groups and 92.8%